2018
DOI: 10.3389/fdigh.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

Building and Sustaining Diverse Functioning Networks Using Social Media and Digital Platforms to Improve Diversity and Inclusivity

Abstract: There has long been a focus on building inclusion and diversity in the sciences through a range of efforts intended to increase representation and access. Despite expansive efforts supported by higher education institutions, funding agencies and others, a need persists to support broad participation and success. Digital platforms, including blogs, and social media such as Twitter TM , offer emergent paths for scientists to proactively build supportive communities, even where structural diversity or numerical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…The consideration of media as a potential pathway for mentorship may represent a more novel and modern approach to mentor interactions. The current generation of students, and minority students in particular, are spending a large percentage of their time interacting with media (Montgomery, 2018;Pew Research Center, 2019). We found that women and students of color are relatively familiar with minority social media influencers, but may not have been exposed to media depictions of minority female STEM professionals to the same extent.…”
Section: Resultsmentioning
confidence: 99%
“…The consideration of media as a potential pathway for mentorship may represent a more novel and modern approach to mentor interactions. The current generation of students, and minority students in particular, are spending a large percentage of their time interacting with media (Montgomery, 2018;Pew Research Center, 2019). We found that women and students of color are relatively familiar with minority social media influencers, but may not have been exposed to media depictions of minority female STEM professionals to the same extent.…”
Section: Resultsmentioning
confidence: 99%
“…This series was sponsored by Kelly Doran and organized by Lindsey Burcham and Brady Spencer at the University of Colorado Anschutz Medical Campus (CU-AMC) in Aurora, CO. To reach scientists with a particular interest in streptococcal research, the seminar was advertised by e-mail to the previous attendees and registered attendees for the 2018 and 2020 Streptococcal Biology GRC/GRS, respectively. In an attempt to attract a broad and diverse audience, the organizers also advertised through social media platforms (Twitter and Facebook) ( 6 ). On Twitter, the organizers primarily interact with other academic scientists, while the organizers’ Facebook accounts primarily reach social contacts; however, overlap exists in the networks across the two platforms.…”
Section: Methodsmentioning
confidence: 99%
“…A report from the US National Academies of Sciences underscored the importance of intentional and inclusive mentoring for positive personal and professional growth (NASEM, 2019). The report recommends changes to institutional structures and cultures to better support commitments to effective mentorship and adoption of collective or group mentoring and mentoring networks (Montgomery and Page, 2019), which can help diffuse power imbalances in the more traditional one-to-one mentoring relationships, as well as more independent funding support for students and earlycareer researchers. In addition, universities need to destigmatize mental health and provide more support services.…”
Section: Hierarchical Power Dynamicsmentioning
confidence: 99%
“…Some organizations were started directly through building community via social media, like Ge-oLatinas. While recognizing that an increased online presence raises exposure to targeted harassment and other hos-tility, social media can serve as a transformational platform for building community and sharing of resources and experiences beyond institutional, disciplinary and national boundaries (Montgomery, 2018;Britton et al, 2019). Social media is facilitating relationship building across organizations and networks especially among early-career geoscientists, who are leading actions for change in the discipline.…”
Section: Building Community Through Peer-mentoring Networkmentioning
confidence: 99%